Padrão de especialização e competitividade das exportações de Minas Gerais no período recente - Silva, Karine Aparecida Obalhe da (2007)
The present work has the Minas Gerais especialization pattern of exportations as study object and it has as general objective analyze the more dinamic productive sectors of Minas Gerais State, as well to understand the composition of the Minas Gerais exportation guideline, in the phase of commercial opening, according to some statistics of the competitiveness and the Pavitt tipology (tecnolgical exportations intensity). The results ratify the general hypothesis of this work, which is the predominancy of exportation sectors based on natural resources in the guideline mencioned. Thus, observing the factorial intensity of the Minas Gerais State exportations, we perceive that the specialized international sectors commercial sectors deal just with tradicional (and not dynamic) comparative advantagens. Moreover, analyzing the tecnolgical exportations intensity, we observe that, in the context of commercial opening, there have not been changing exportations pattern for more intensive sectors in technology. In another terms, the inovations search by P&D increments didn t occurred, at least of intense form, at the Minas Gerais economy exportations level.